Assessment of the Student Services of De La Salle University Dasmariñas College of Education Graduate Studies: Basis for a Proposed Enhancement Program - Salasbar, Marites S.; Creus, Mark Airon P.; Dumo, Irlo L.; Campos, Laura R.; Buenaobra, Tita B.; Gatpandan, Mary Ann B.; Guimary, Nancy R. (ASEAN Journal of Education, 2017)
The study aims to assess the student services of the College of Education Graduate Studies (COEGS) of De La Salle University Dasmariñas for a proposed enhancement program. The main sources of data came from the graduate students of the College of Education enrolled in the 2015-2016 academic year. A validated questionnaire was designed, highlighting the different student services of the college. Findings from the study showed that the students were very familiar with the library, canteen or food services, bookstore, payment centers and classrooms. However, students were somewhat familiar with the university clinic and campus ministry office. In terms of extent of usage, the results showed that students always used the classroom and canteen services. However, they rarely used the University Research Office (URO), University Clinic, and Campus Ministry Office. With regard to the level of satisfaction, findings show that the students were very satisfied with the classrooms and physical maintenance and cleanliness services of the university. However, students were dissatisfied with the services of the university clinic and campus ministry office. These findings demonstrate the need to have an Action Plan for the Student Services Enhancement Program which will help improve students’ level of familiarity, extent of usage and level of satisfaction with all the student services being offered by the College of Education Graduate Studies of De La Salle University Dasmariñas.